Isolation of lactic acid bacteria as potential probiotic candidates from the digestive tract of Gobiopterus sp. - MIKKA HAKKINEN; ABDUL RAHEM FAQIH; ASEP AWALUDIN PRIHANTO; SEPTI ANITASARI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Hakkinen M, Faqih AR, Prihanto AA, Anitasari S. 2025. Isolation of lactic acid bacteria as potential probiotic candidates from the digestive tract of Gobiopterus sp. Biodiversitas 26: 1008-1017. The distinctive ecological niche presented by the volcanic Lake Ranu Grati offers a fascinating setting for the exploration of microbial diversity, with a particular focus on lactic acid bacteria (LAB), which are renowned for their advantageous characteristics and hold significant promise as potential probiotics. The fish species Gobiopterus sp., which resides within this lake, presents a compelling opportunity for the isolation of novel strains of lactic acid bacteria (LAB). The objective of this study was to isolate and characterize probiotic bacteria from the digestive system of Gobiopterus sp. and to find bacterial strains that can improve aquaculture cultivation, health, and disease resistance. This study obtained 30 bacterial isolates originating from the digestive tract of Gobiopterus sp., of which 8 isolates were Gram-positive and catalase-negative. These isolates showed the ability to tolerate acid and bile salts which were one of the properties for probiotic candidates. Antibacterial activity varied among the isolates, with some showing significant inhibition against Aeromonas hydrophila, Vibrio alginolyticus, and Vibrio harveyi. Enzyme activity test found that the selected isolates can produce protease and cellulase enzymes. The selected isolates had sufficient hydrophobicity properties ranging from 23-41% and the DNA sequencing results identified the 3 isolates as the member of genus Enterococcus. The results of this study yielded isolates that have the potential as probiotics in the field of aquaculture. Therefore, further research should be conducted for the comprehensive characterization and safety assessment required for the use of probiotic bacteria.